Pengembangan Model Pembelajaran Reflektif Untuk Program Studi Profesi Dokter: Enam Langkah Pembelajaran Reflektif Klinik - Eti Poncorini Pamungkasari; Amitya Kumara; Armis Armis; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: Reflection is one of important skills to be possessed by medical professional, which should be developed while studying at medical faculty. In clinical stage of medical education in many medical schools in Indonesia, a reflection-learning model has not developed yet. This often make clinical teacher confuse, how to facilitate the reflection learning correctly.Methods: We developed the reflection-learning model for clinical stage of medical education. The model development was started with a blueprint and a model’s draft development, which referred by reflection learning theory. The next step was a clinical teacher panel discussion and in-depth interviews of medical education experts. After these process, a reflective clinical learning model were developed and six clinical teachers were involved in the models’ trial. They adopted the model in their learning sessions. In-depth interviews were used to explore clinical teachers’ experience when they implemented the model.Result: a six-step clinical reflection learning model developed, consists of (1) case selection, (2) case presentation, (3) self-evaluation, (4) peers’ feedback, (5) teachers’ feedback and (6) reflection writing. The implementation problem is that students and lectureres have not been accustomed to reflective learning and lecturers’ limitation of time. Conclusion: This study shows that the six steps clinical reflection learning model could be used as an alternative learning method of reflection learning. However, in practice, both clinical teachers and students should have sufficient understanding about the model, and clinical teacher should provide sufficient time in the learning process.